Yearly Height Gain Is Dependent on the Truly Received Dose of Growth Hormone and the Duration of Periods of Poor Adherence: Practical Lessons From the French Easypod™ Connect Multicenter Observational Study - Coutant, Régis; Nicolino, Marc; Cammas, Benoit; de Buyst, Valérie; Tauber, Maïthé; Hamel, Jean-François (Frontiers in Endocrinology, 2022)
Objective To study the impact of the true mean daily dose and the true mean number of injections per week on the yearly height gain in short children treated with recombinant human growth hormone (rhGH). Design and Methods 220 children from the French Easypod™ Connect Observational Study (ECOS) used the Easypod™ electronic device to record rhGH injections. The mean daily rhGH dose (the sum of the doses truly received divided by the number of days) and mean number of injections per week (the number of injections truly performed divided by the number of weeks) were calculated. Linear mixed models were used to study the impact of short (3-month) and long (1-year) variations in rhGH administration on the yearly height change [as a standard deviation score (SDS)], with time on treatment as a covariate. For each patient, several periods of 3 or 12 months were considered and designated as poorly adherence or fully adherence. We studied the impact of each of period on the height change. Results At treatment initiation, the mean ± SD age was 9.8 ± 3.7 years (females: 47%, prepubertal: 86%) and the mean height was -2.28 ± 0.92 SDS. The mean treatment duration was 3.2 ± 1.1 years (685.2 patient years). 122 patients were GH-deficient, 79 were small for gestational age, and 19 had Turner syndrome. When treatment was computed over 12-month periods, receiving a mean daily dose <0.03 mg/kg.d was associated with a 20% lower mean yearly height gain SDS when<3 injections/week were received (vs.>5 injections/week), whereas maintaining a mean daily dose >0.03 mg/kg.d with<3 injections/week was not associated with a lower yearly height gain SDS (vs.>5 injections/week). For 3-month periods, changes in the daily rhGH dose or the number of injections per week over such short period did not influence the yearly height gain SDS. Conclusion The 12-month treatment model showed that when poor adherence leads to a low true daily GH dose, the yearly height gain is low. The 3-month treatment model showed that poor adherence for short periods (<3 months) had no impact on the height SDS.